Deep inspirational breath hold to reduce cardiac dose in left-sided breast radiotherapy. Issue 3 (22nd June 2017) - Welgemoed, Camarie; Rogers, Jonathan; McNaught, Patti; Cleator, Susan; Riddle, Pippa; Gujral, Dorothy
Abstract: Background: During left-sided breast radiotherapy, the heart is often exposed to radiation dose. Shielding can be utilised to reduce heart exposure, but compromises the dose delivered to the breast tissue and, in a proportion of patients, to the tumour bed. Deep inspiration breath hold (DIBH) can be used as a technique to move the heart away from the treatment area and thus reduce heart dose. This study examines the efficacy of the Elekta Active Breathing Coordinator (ABC), a DIBH method, in reducing heart dose. Materials and methods: In total, 12 patients receiving radiotherapy to the left breast were planned for treatment with both a free-breathing (FB) and an ABC scan. The dose volume histogram data for the plans was analysed with respect to heart V13, V5 Gy, mean heart dose and ipsilateral lung V18 Gy. Tumour bed D98%, threshold lung volume in breath hold (BH) and the maximum BH time for each patient was also measured. Patients then received their radiotherapy treatment using the ABC plan and the systematic error in the craniocaudal, lateral and vertical axes was assessed using orthogonal imaging. Results: The median heart V13 Gy for FB and DIBH patients was 3% (range, 0·85–11·28) and 0% (range, 0–1·56), respectively, with a mean heart dose of 2·62 Gy (range, 1·21–4·93) in FB and 1·51 Gy (range, 1·17–2·22) in ABC. The median lung V18 Gy was 8·7% (3·08–14·87) in FB plans and 9% (4·88–12·82) in ABC plans. The mean systematic set-up errors in all three planes were within the departmental set-up tolerance of 5 mm for both techniques. Median FB tumour bed D98% was 97·4% (92·8–99·5) and 97·5% (97·3–98·5) for ABC. Conclusion: ABC represents a good method of reducing radiation dose to the heart while not compromising on dose to the tumour bed, and it has a clear advantage over FB radiotherapy in reducing the risk of cardiac toxicity. It is tolerated well by patients and does not produce any difficulties in patient positioning.